CFU counts of Vibrio spp. on seaweeds and water column at 16°C and 20°C - Wilson, Sidney; Saha, Mahasweta (PANGAEA, 2025)
We investigated the impact of elevated water temperatures on the abundances of pathogenic Vibrio species associated with seaweeds and coastal waters. Three seaweed species - Fucus serratus, Palmaria palmata, and Ulva spp.- were collected from Plymouth Sound, United Kingdom, and used in a mesocosm experiment conducted at Plymouth Marine Laboratory in June 2024. The samples were exposed to two temperature treatments (16 °C and 20 °C) for seven days each to simulate warming ocean conditions. After the seven-day treatments, microbial suspensions (referred to as microbial soups) were prepared from each seaweed replicate and corresponding water column sample. These suspensions were filtered and incubated on ChromAgar Vibrio chromogenic media plates for 72 hours to selectively identify and differentiate Vibrio parahaemolyticus, Vibrio alginolyticus, and Vibrio vulnificus/cholerae. Colony-forming units (CFUs) were counted for each replicate, providing quantitative data on the response of these Vibrio species to elevated temperatures.
Keywords: Laboratory experiment; mesocosm experiment